Immune RECIST criteria and symptomatic pseudoprogression in non-small cell lung cancer patients treated with immunotherapy - Vrankar, Martina (Radiology and oncology (Ljubljana), 2018)
Uncommon responses during immunotherapy is a new challenging issue in oncology practice. Recently, new criteria for evaluation of response to immunotherapy immune response evaluation criteria solid tumors (iRECIST) were accepted. According to iRECIST, worsening of performance status (PS) accompanied to pseudoprogression reflects most probably the true progression of the malignant disease. Methods. A systematic review of the literature was made by using several electronic database with the following search criteria: symptomatic pseudoprogression, atypical response, immunotherapy and lung cancer. Results. In the literature, we identified five reports of seven patients treated with immunotherapy that met the inclusion criteria. We also report our experience of patient with pseudoprogression and almost complete response after one dose of immunotherapy. Conclusions. As seen from our review, iRECIST criteria might be insufficient in distinguishing true progression from pseudoprogression in some patients with advanced NSCLC treated with immunotherapy. More precise assessment methods are urgently needed.
Keywords: atipičen odgovor; imunoterapija; pljuča; rak (medicina)